A Review on Prevalence of Inflammatory Bowel Disease in India - Abhirami, N R; Laksmi, V V; Deepitha, A M (Journal of Drug Delivery and Therapeutics, 2022)
Inflammatory bowel disease (IBD) including ulcerative colitis (UC) and Crohn’s disease (CD) was believed to be a Western disease, but are now increasingly being reported from India and other Asian countries where IBD was almost unheard of 30 years ago. Now India is projected to have one of the highest IBD burden across the world. There is rising incidence and prevalence of IBD in India topping the Southeast Asian countries. The clinical presentation of IBD in India is similar to other South East Asian countries. IBD is considered as a result of the complex interaction between the environment, diet, certain medications, genetic variables and a severe autoimmune response against normal bacteria in the gut. However exact cause is still unknown. Also there exists a gender distribution in IBD. In India IBD is more prevalent in males compared to females. This review summarizes the prevalence of IBD in India and some possible risk factors contributing to it.Keywords: Inflammatory bowel disease, prevalence, India